CLPP inhibition triggers apoptosis in human ovarian granulosa cells via COX5A abnormality–Mediated mitochondrial dysfunction - Yuan, Xiong; Ma, Wenjie; Chen, Shuping; Wang, Huiyuan; Zhong, Chenyi; Gao, Li; Cui, Yugui; Pu, Danhua; Tan, Rongrong; Wu, Jie (Frontiers in Genetics, 2023)
Premature ovarian insufficiency (POI) is characterized by early loss of ovarian function before the age of 40 years. It is confirmed to have a strong and indispensable genetic component. Caseinolytic mitochondrial matrix peptidase proteolytic subunit (CLPP) is a key inducer of mitochondrial protein quality control for the clearance of misfolded or damaged proteins, which is necessary to maintain mitochondrial function. Previous findings have shown that the variation in CLPP is closely related to the occurrence of POI, which is consistent with our findings. This study identified a novel CLPP missense variant (c.628G > A) in a woman with POI who presented with secondary amenorrhea, ovarian dysfunction, and primary infertility. The variant was located in exon 5 and resulted in a change from alanine to threonine (p.Ala210Thr). Importantly, Clpp was mainly localized in the cytoplasm of mouse ovarian granulosa cells and oocytes, and was relatively highly expressed in granulosa cells. Moreover, the overexpression of c.628G > A variant in human ovarian granulosa cells decreased the proliferative capacity. Functional experiments revealed that the inhibition of CLPP decreased the content and activity of oxidative respiratory chain complex IV by affecting the degradation of aggregated or misfolded COX5A, leading to the accumulation of reactive oxygen species and reduction of mitochondrial membrane potential, ultimately activating the intrinsic apoptotic pathways. The present study demonstrated that CLPP affected the apoptosis of granulosa cells, which might be one of the mechanisms by which CLPP aberrations led to the development of POI.